The Use of Endobronchial Ultrasound in the Diagnosis of Subacute Pulmonary Histoplasmosis. (12th October 2015) - Egressy, Katarine von Lang; Mohammed, Mohammed; Ferguson, J. Scott
Abstract : Objective . Endobronchial ultrasound (EBUS) utility in diagnosis in malignant and granulomatous mediastinal disease has been well demonstrated. We propose to examine the role of EBUS transbronchial needle aspiration (EBUS-TBNA) in the diagnosis of subacute pulmonary histoplasmosis (SPH) with mediastinal lymphadenopathy in an area where histoplasmosis is endemic. Methods . A retrospective review was performed in a single academic institution between 2009 and 2012 of patients referred for EBUS-TBNA who had radiographic imaging and clinical symptomatology suspicious for SPH. Seven patients were reviewed. TBNA results showing granulomatous disease with areas of necrosis in the appropriate clinical setting were considered to be adequate for the diagnosis of SPH when alternative diagnosis was excluded. Patients underwent further clinical follow-up of 12 months to determine the final diagnosis. Results . All seven patients were felt to have SPH diagnosis reached by a combination of clinical presentation, EBUS-TBNA results, fungal serologies, and antigen testing. None of the patients needed further invasive procedures. Conclusions . EBUS-TBNA is a minimally invasive tool that can be used to support a diagnosis of SPH in patients with a high degree of clinical suspicion. EBUS-TBNA should be considered as an adjunctive diagnostic procedure for patients with SPH in an appropriate clinical setting.